Focus group on conflict management in the classroom in Secondary Education in Costa Rica: mixed methods approach - Bonilla R., Pedro; Armadans, Immaculada; Anguera, M. Teresa (Frontiers in Psychology, 2024)
The educational system in Costa Rica, as regulated by Law #7727, which governs Alternative Conflict Resolution and Promotion of Social Peace. must consider the interplay of various factors influencing classroom conflicts and the management strategies employed by teachers. Consequently, it becomes imperative to identify the most effective conflict resolution practices applicable within this context. To achieve this, a thorough procedure based on mixed methods was employed to analyze and interpret both classroom conflict behaviors and teachers' strategic responses.This study employed an indirect observational methodology, from a mixed methods approach. Data was collected through a focus group comprised of teachers.Following the connect framework, the procedure was conducted in three phases: QUAL-QUAN-QUAL.Two analytical techniques were implemented. A lag sequential analysis was employed used to explore potential behavioral patterns. The results of this analysis informed a polar coordinate analysis, which generated a visual representation of the relationships between codes.A focus group addressed four questions, yielding satisfactory data quality control results (kappa values: 0.80, 0.77, 0.76, 0.82).In polar coordinate analysis, the 37 observational instrument categories were designated as focal behaviors. Each of the 37 analyses treated all categories as conditioned behaviors.The analysis identified 342 activation/inhibition relationships between focal and conditioned behaviors. Of these, 195 were statistically highly significant, distributed across quadrants: Quadrant I (106), Quadrant II (36), Quadrant III ( 16), Quadrant IV (36).Significant gaps in understanding of conflict were identified, along with disparities in the resources and competencies necessary for successful conflict resolution among the observed educators. Specifically, teachers frequently employed techniques informed by intuition rather than deliberate strategy learned in their training. Consequently, the study advocates for enhancing teachers' cognitive and emotional competencies to optimize conflict management within the classroom and bolster their adaptive coping mechanisms.